A comparison of mesospheric and low‐thermospheric winds measured by Fabry‐Perot interferometer and meteor radar over central China. Issue 10 (1st October 2016) - Yu, Tao; Xia, Chunliang; Zuo, Xiaomin; Huang, Cong; Mao, Tian; Liu, Libo; Liu, Zhizhao
Abstract: Wind data observed by a Fabry‐Perot interferometer (FPI) and a meteor radar (MR) deployed in two stations, which are 430 km apart in ground distance, are used to study wind climatology in mesosphere/lower thermosphere over central China and compare between the measurements. A general morphologic similarity of the FPI winds and MR winds is identified with 4 year data since November 2011. At 87 km, the wind vector plots show that the FPI and MR winds agree with each other very well in all months. The zonal winds of both instruments have an apparent semiannual variation with a maximal strength of −20 m/s at around 18:00 UT in equinoctial months, and the meridional winds from both instruments have an apparent annual variation with a maximal strength of −40 m/s at around 15:00 UT in summer months. The correlation coefficients between the measurements of the two instruments are about 0.95 for meridional wind and 0.90 for zonal wind. At 97 km, the wind vector plots show that FPI and MR winds agree with each other from May to October and are obviously different in the rest months. There are very weak semiannual variations at around 18:00 UT for both zonal winds and pronounced annual variation at around 13:00 UT for both meridional winds. The correlation coefficients between the FPI and MR winds are 0.73 for zonal wind and 0.86 for meridional wind, which are overall smaller than that at 87 km. A Gaussian distribution of airglow profile is used to investigate the deviations associated with peak height and full width at half maximum (FWHM) of airglow layer. It is found that the variation of peak height could lead to about 20% variation of correlation coefficients between measurements at the height of 87 km and about 14.8% at the height of 97 km on average. The variation of FWHM could lead to a correlation coefficient variation of about 2.4% and 3.5% at the height of 87 km and 97 km, respectively. Some other reasons, such as the influence of geomagnetic field on meteor trail and the propagation of gravity waves, could also contribute to these differences between measurements. Key Points: Over 4 year comparison of FPI and meteor radar wind over China Correlation coefficient of FPI/MR wind stronger for meridional than zonal stronger at 87 km than 97 km Influence of airglow variation on FPI wind